Packaging para productos artesanales de cacao, elaborados por los pequeños agricultores de la comunidad las delicias, Provincia de Esmeraldas - Gorozabel Obando, Ximena Melissa (2018)
The present project intended to introduce the handmade of cocoa products elaborated by Las Delicias community farmes, to distribute in the market, it contributes with development of the popular and solidary economy of the place. The lack of a package that protects and identifies different products made from 100% fine cocoa; aroma such as: granola, cocada, tablets and wine; demand the need to develop a packaging with technical and design characteristics, using identifying elements of the community. The objective of this job is to present a package with a ideal technical and design characteristics for commercialization of Las Delicias community cocoa products. The methodology of this project was framed on bibliography, investigation and field, qualitative approach because information was collected on each of the topics to development the proposal. While the applied design method consists on packaging development of that reflects the community identity. The techniques applied were interviews and focus group, the instruments used were questionnaire guide and result was obtained for the creation of the packaging. The development of this creative proposal is essential, from the graphic side; it allows to contribute community projects through an adequate packaging for handmade products, helping the economy development. This project contributes to the conservation, protection, communication and identification of handmade products of cocoa though a dynamic workflow, using the same graphic line and materials from community´s environment. At technological aspect it was used a camera, tripod, microphone to document the creative process of designing packaging, at the same way an alternative printing process was used and it was searched for the whole set of elements actual of all the collected information, to be judged by the audience target of handmade products